1993
DOI: 10.1073/pnas.90.8.3299
|View full text |Cite
|
Sign up to set email alerts
|

Persistent induction of c-fos and c-jun expression by asbestos.

Abstract: To investigate the mechanisms of asbestos-induced carcinogenesis, expression of c-fos and c-jun protooncogenes was examined in rat pleural mesothelial cells and hamster tracheal epithelial cells after exposure to crocidolite or chrysotile asbestos. In contrast to phorbol 12-myristate 13-acetate, which induces rapid and transient increases in c-fos and c-jun mRNA, asbestos causes 2- to 5-fold increases in c-fos and c-jun mRNA that persist for at least 24 hr in mesothelial cells. The induction of c-fos and c-jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(98 citation statements)
references
References 24 publications
3
94
0
1
Order By: Relevance
“…Heinz et al discovered increased transcription of c-fos and c-jun in rat pleural mesothelial cells exposed to crocidolite asbestos (38). We have preliminary evidence for increased expression of p53 protein in response to crocidolite asbestos fibers.…”
Section: Introductionmentioning
confidence: 51%
“…Heinz et al discovered increased transcription of c-fos and c-jun in rat pleural mesothelial cells exposed to crocidolite asbestos (38). We have preliminary evidence for increased expression of p53 protein in response to crocidolite asbestos fibers.…”
Section: Introductionmentioning
confidence: 51%
“…As reported above, asbestos stimulates the expression of c-fos and c-jun mRNA in mesothelial cells in a dose-dependent fashion (Heintz et al, 1993;Ramos-Nino et al, 2002). One of the mechanisms by which VEGF and PlGF elicit biological responses is the induction of Fos-B and c-Fos expression in endothelial cells and monocytes (Holmes & Zachary, 2004).…”
Section: Cooperation Between Asbestos and Angiogenic Growth Factors Imentioning
confidence: 68%
“…Finally, in mesothelial and lung epithelial cells asbestos fibers, as opposed to nonpathogenic minerals, cause a persistent induction of the redox-sensitive transcription factors NF-κB and Activator Protein-1 (AP-1), which is accompanied by chronic alterations in gene expression (Heintz et al, 1993;Janssen et al, 1995). As mentioned above, the aberrant activation of the NF-κB pathway is regarded as a critical event for mesothelial cell transformation (Toyooka et al, 2008).…”
Section: Reactive Oxygen and Nitrogen Species (Ros/rns)mentioning
confidence: 99%
See 1 more Smart Citation
“…JUN is a transcription factor and functions as homo-or hetero-dimerization with FOS to form the transcription factor AP-1, which can bind to the promoter region of intermediate genes involved in cell division and other cell functions. Both crocidolite and chrysotile asbestos reportedly caused increases in the expression of JUN and FOS in rat pleural mesothelial cells [29]. Since the gene amplification of JUN was identified in a subset of MPM tumors, it was suggested that there were some strong and persistent factors for JUN activation during the development of MPM tumor cells.…”
Section: Searching For New Key Genes In Malignant Mesotheliomamentioning
confidence: 99%